International core curriculum for capsule endoscopy training courses - Fernández-Urién, Ignacio; Seitz, Uwe (Endoscopy International Open, 2017)
Capsule endoscopy (CE) has become a first-line noninvasive tool for visualisation of the small bowel (SB) and is being increasingly used for investigation of the colon. The European Society of Gastrointestinal Endoscopy (ESGE) guidelines have specified ...